Politics at the Concert: Or How did a Political Party Called “There is Such a People” Win the Hearts of Voters? (Seminar_BG, 2023)
This article aims to explain the mass support of citizens for the newly emerged political party “There is Such a People”, whose chairman is the famous Bulgarian public singer, TV host, showman and producer Slavi Trifonov. “There is Such а People” managed to win the Bulgarian parliamentary elections in 2021, replacing the leading long-ruling party GERB. The analysis focuses on the discourses structuring the dramaturgy of the concerts of Slavi Trifonov’s band – the Ku-Ku Band, used in his election campaign but also performed outside Bulgaria to the emigrated Bulgarians whose vote was decisive for his victory in the parliamentary elections. These discourses contain political messages, shaped as a cultural musical product and, respectively, referred to a certain way of making sense of the audience that became voters. They also set the structure of Slavi Trifonov’s autobiographical books, the analysis of which complements the interpretation of the Ku-Ku Band’s concerts in the text. The main thesis is that we cannot understand the phenomenon of Slavi Trifonov and the Ku-Ku Band if we do not place them in a post-socialist context where socialist cultural policies still resonate, but where the market of culture and the boundary between high and popular culture have yet to emerge.  ReferencesBourdieu, Pierre. 1984. Distinction: A Social Critique of the Judgment of Taste. Cambridge, Massachusetss: Harvard University Press.Dichev, Ivaylo. 2016. Kulturata kato distantsia. Edinadeset eseta po kulturna antropologia. Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“.Dimov, Ventsislav. 2001. Etnopopbumat. Sofia: Balgarsko muzikoznanie.Dimov, Ventsislav. 2019. Muzikata za naroda na mediynia front (Mekata vlast na narodnata i populyarnata muzika v sotsialisticheska Bulgaria). Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“.Dobrev, Petar. 2015. „Chalgata e pederastki moment v zhivota na selyandura“. V: Genova, Neda, Dinev, Ivaylo, Dobrev, Petar, Dodov, Stanislav, Samokovska, Irina, Tsvetkov, Chavdar (eds.) Diversia: V opit za po-dobar proval. Sofia: Roprint.Elenkov, Ivan. 2008. Kulturniyat front. Balgarskata kultura prez epohata na komunizma – politichesko upravlenie, ideologicheski osnovania, institutsionalni rezhimi. Sofia: Ciela.Elenkov, Ivan. 2013. Trud, radost, otdih i kultura. Vavedenie v istoriyata na ideologicheskoto modelirane na vsekidnevieto prez epohata na komunizma. Sofia: Tsentar za akademichni izsledvania, Riva.Hristov, Todor. 2013. Svoboda i suverennost v Aprilskoto vastanie. Sofia: FHSI/ Iztok–Zapad.Kabakchieva, Petya. 2016. Komunisticheski modernosti. Balgarskiyat komunizam. Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“.Laclau, Ernesto. 2005. On Populist Reason. London, New York: Verso.Laclau, Ernesto; Mouffe, Chantal. 2001. Hegemony and Socialist Strategy. Towards a Radical Democratic Politics. London, New York: Verso.Mineva, Mila. 2016. Vizualnoto konstruirane na sotsialisticheskoto potreblenie. (unpublished doctoral dissertation).Ragaru, Nadezh. 2010. Prepletenite vremena na nastoyashteto. Bulgaria 20 godini sled 89-ta. Sofia: Kritika i humanizam.Statelova, Rosmary. 2005. The Seven Sins of Chalga. Sofia: Prosveta.Trifonov, Slavi, Dilov-sin, Lyuben. 2002. Slavi Trifonov za starchaneto. Negovite zhivot, istorii, pouchenia, teorii i natyakvania, zapisani ot Lyuben Dilov-sin. Sofia: Ciela.Trifonov, Slavi, Siromahov, Ivo. 2015. Slavi Trifonov za men e chest. Otkroveniyata na Slavi Trifonov, zapisani ot Ivo Siromaho. Sofia: Ciela.
Keywords: concert; music; popular music; chalga; postsocialism; socialism